My Teaching Philosophy: Theoretical Musings of a South Asian-educated Instructor at an American University - Paudel, Jagadish (Journal of NELTA, 2020)
For a prospective teacher at almost any level, clearly defining one’s teaching philosophy has long been a mandatory requisite for applying and obtaining a teaching position in the US schools and colleges. However, in Nepal, this requirement is as yet unknown, and the demand to define one’s teaching philosophy and set it to writing may pose a novel challenge for even the most experienced and cherished educator. In this paper, along with briefly introducing the current North American theory of teaching philosophy, I present a statement of my teaching philosophy, my evolving beliefs towards teaching writing, and my personal approach to teaching writing. Finally, I theorize my philosophy of teaching, drawing ideas from some renowned critical pedagogy scholars. I believe that these musings are worthy of reading for prospective and experienced educators who have not yet systematized their teaching philosophy, specifically, teachers of English who teach or wish to teach writing courses, stimulating them to be more closely focused on their approach to teaching and to carefully situate their teaching-learning activities within their teaching philosophies.